Chromolaena odorata fallows - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Chromolaena odorata fallow in food cropping systems: an agronomic assessment in southwest Ivory Coast by J J P Slaats 177pp ISSN 0926 9495